Դրացիությունը հայոց ավանդական եւ արդի կենցաղում - Ստեփանյան, Արմենուհի
The neighbourship is a very important component of the public life of the Armenians. Neighbourship is a formation for years and is a regulate system of reciprocal relations between men and families, living side by side. The neighbourship is preserved up today and is still going on. To help each other in different situations (happinesess or sadness) of life is characteristic to a neighbour in old times as well as in our days. That is why the Armenians say. “The nearist neighbor is better, than the distant relative”. Соседство является очень важным компонентом в общественной жизни армян. Соседские отношения формируется годами и регулируют взоимоотношения между людьми и семями, которые живут бок о бок. Традиционная система соседства сохранилась вплоть до наших дней и актуален сегодня. Помогать друг другу в разных ситуациях жизни (в беде да в счастье) самая характерная черта соседа как в давних временах так и в наших дней. Вот почему армянин говорит: «Близкий сосед лучше дальнего родственника».
Keywords: Հայաստան; Կենցաղավարություն